Improving the reactivity of a former ground sugarcane bagasse ash produced by autogenous combustion through employment of two different additional grinding procedures - Moraes, J. C.B.; Cordeiro, G. C.; Akasaki, J. L. [UNESP]; Vieira, A. P.; Payá, J. (Elsevier, 2021)
Studies on reactivity of sugarcane bagasse ash (SCBA), obtained by an autogenous combustion process, with low loss on ignition and three different particle sizes were carried out (SCBA-1, SCBA-2 and SCBA-3). The ashes were characterized by their particle size distribution, chemical composition, X-ray diffraction (XRD), thermogravimetric analysis (TGA) and field emission scanning electron microscopy (FESEM). The ash with lowest particle size was SCBA-3, followed by SCBA-2, which both were finer than SCBA-1. Calcium hydroxide/SCBA blends were assessed by means of loss of electrical conductivity (Lc), TGA and FESEM. Portland cement/SCBA pastes were analyzed through isothermal calorimetry, TGA, FESEM and compressive strength. Results showed that SCBA with lowest particle size (SCBA-3) presented highest reactivity, which resulted in statically significant better compressive strength than that of control paste (with only Portland cement) after 28 days of curing. The improvement on compressive strength by employing SCBA-3 respect to control and SCBA-1 were 17.9 and 14.1%, respectively, after 180 days of curing.
Keywords: Calcium hydroxide/pozzolan paste; Compressive strength test; Microstructural study; Portland cement/pozzolan paste; Pozzolan characterization